Tumorigenic functions of serglycin: Regulatory roles in epithelial to mesenchymal transition and oncogenic signaling. (May 2020) - Manou, Dimitra; Karamanos, Nikos K.; Theocharis, Achilleas D.
Abstract: Numerous studies point out serglycin as an important regulator of tumorigenesis in a variety of malignancies. Serglycin expression correlates with the aggressive phenotype of tumor cells and serves as a poor prognostic indicator for disease progression. Although serglycin is considered as an intracellular proteoglycan, it is also secreted in the extracellular matrix by tumor cells affecting cell properties, oncogenic signaling and exosomes cargo. Serglycin directly interacts with CD44 and possibly other cell surface receptors including integrins, evoking cell adhesion and signaling. Serglycin also creates a pro-inflammatory and pro-angiogenic tumor microenvironment by regulating the secretion of proteolytic enzymes, IL-8, TGFβ2, CCL2, VEGF and HGF. Hence, serglycin activates multiple signaling cascades that drive angiogenesis, tumor cell growth, epithelial to mesenchymal transition, cancer cell stemness and metastasis. The interference with the tumorigenic functions of serglycin emerges as an attractive prospect to target malignancies.